Molecular Mechanisms of Cadherin Function During Cortical Migration - Martinez-Garay, Isabel (Frontiers in Cell and Developmental Biology, 2020)
During development of the cerebral cortex, different types of neurons migrate from distinct origins to create the different cortical layers and settle within them. Along their way, migrating neurons use cell adhesion molecules on their surface to interact with other cells that will play critical roles to ensure that migration is successful. Radially migrating projection neurons interact primarily with radial glia and Cajal-Retzius cells, whereas interneurons originating in the subpallium follow a longer, tangential route and encounter additional cellular substrates before reaching the cortex. Cell-cell adhesion is therefore essential for the correct migration of cortical neurons. Several members of the cadherin superfamily of cell adhesion proteins, which mediate cellular interactions through calcium-dependent, mostly homophilic binding, have been shown to play important roles during neuronal migration of both projection neurons and interneurons. Although several classical cadherins and protocadherins are involved in this process, the most prominent is CDH2. This mini review will explore the cellular and molecular mechanisms underpinning cadherin function during cortical migration, including recent advances in our understanding of the control of adhesive strength through regulation of cadherin surface levels.